2020
DOI: 10.1136/bmjopen-2020-040487
|View full text |Cite
|
Sign up to set email alerts
|

COVID-19 prevention and treatment information on the internet: a systematic analysis and quality assessment

Abstract: ObjectiveTo evaluate the quality of information regarding the prevention and treatment of COVID-19 available to the general public from all countries.DesignSystematic analysis using the ‘Ensuring Quality Information for Patients’ (EQIP) Tool (score 0–36), Journal of American Medical Association (JAMA) benchmark (score 0–4) and the DISCERN Tool (score 16–80) to analyse websites containing information targeted at the general public.Data sourcesTwelve popular search terms, including ‘Coronavirus’, ‘COVID-19 19’, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
56
0
2

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 67 publications
(68 citation statements)
references
References 57 publications
2
56
0
2
Order By: Relevance
“…We observed similar results in the second PLifeCOVID-19 Study, in which higher percentage of respondents declared the introduction of supplementation with immune-related nutrients and compounds during the first wave of the pandemic (and lockdown), when COVID-19 cases and deaths in Poland were incomparably lower than in the second wave during autumn. Previous GT analysis and population-based studies revealed that the interests [ 48 , 49 , 50 ] and practices [ 51 ] of protective behaviors, such as hand washing or use of hand sanitizers increased after the COVID-19 outbreak. Moreover, undertaken of those health-protective behaviors was related to a variety of factors, including sociodemographic [ 51 , 52 , 53 ], psychological characteristic (e.g., emotion regulation [ 54 ]), perception of being at risk to get COVID-19 [ 54 ], media or social-media exposure and trust in information from media and other people (friends and bloggers) [ 53 , 55 , 56 ], and knowledge or beliefs about COVID-19 [ 53 ], however there is a limited number of studies comparing both waves of the pandemic [ 54 ].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…We observed similar results in the second PLifeCOVID-19 Study, in which higher percentage of respondents declared the introduction of supplementation with immune-related nutrients and compounds during the first wave of the pandemic (and lockdown), when COVID-19 cases and deaths in Poland were incomparably lower than in the second wave during autumn. Previous GT analysis and population-based studies revealed that the interests [ 48 , 49 , 50 ] and practices [ 51 ] of protective behaviors, such as hand washing or use of hand sanitizers increased after the COVID-19 outbreak. Moreover, undertaken of those health-protective behaviors was related to a variety of factors, including sociodemographic [ 51 , 52 , 53 ], psychological characteristic (e.g., emotion regulation [ 54 ]), perception of being at risk to get COVID-19 [ 54 ], media or social-media exposure and trust in information from media and other people (friends and bloggers) [ 53 , 55 , 56 ], and knowledge or beliefs about COVID-19 [ 53 ], however there is a limited number of studies comparing both waves of the pandemic [ 54 ].…”
Section: Discussionmentioning
confidence: 99%
“…Unfortunately, knowledge about COVID-19 prevention is not fully satisfactory [ 31 , 52 , 62 ] and often derives from social-media or media [ 52 , 62 ]. As it was previously described, Internet information about methods of COVID-19 prevention and treatment, or immune system boosting, including the use of DSs, varies significantly depending on the type of website (e.g., governmental or commercial) and sometimes has an inadequate quality or even presents potentially harmful information quite often [ 14 , 15 , 50 , 63 ]. Interestingly, during lockdown, less respondents from Poland declared to have a contact with DSs advertisements, but more believed that DSs quality was well controlled compared to the pre-pandemic period [ 64 ].…”
Section: Discussionmentioning
confidence: 99%
“…A study of 21 countries found that the number of Google searches for “wash hands” increased with the lower speed of the COVID-19 spread [ 24 ]. However, systematic analyses and quality assessments revealed that considerable amounts of information on COVID-19 on the Internet often lack scientific rigor [ 25 , 26 , 27 , 28 ] and the share of videos contributed by government and health agencies was low [ 29 ]. Sources of COVID-19 information may have an impact on risk perception and self-protection behaviors.…”
Section: Introductionmentioning
confidence: 99%
“…This presents a new challenge to patients with limited clinical understanding, as websites of poorer quality may appear similar to high quality sources of information. The increase in total EQIP score due to higher marks being obtained from the structure domain from the improvement of website quality is a phenomenon which has also been seen in regards to COVID-19 [ 13 ].…”
Section: Discussionmentioning
confidence: 99%
“…Various aspects are considered, such as clarity of information, quality of written work, and website design. The EQIP tool has been used to evaluate information sources related to gallstone disease, transplant surgeries, eczema, liposuction, and, more recently, COVID-19 [9][10][11][12][13], demonstrating its applications across various disciplines and information types. We assessed the top-indexed websites related to appendicitis and appendicectomy using the modified EQIP tool for evaluation.…”
Section: Introductionmentioning
confidence: 99%